2019
DOI: 10.1097/ta.0000000000002373
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hardware failure in patients undergoing surgical stabilization of rib fractures: A Chest Wall Injury Society multicenter study

Abstract: BACKGROUND Surgical stabilization of rib fractures (SSRF) is increasingly used for severe rib fractures/flail chest. There are no reports discussing mechanisms of failure of implanted hardware, its clinical presentation, or consequences. The purpose of this study was to evaluate the incidence, presenting signs, and clinical sequela of hardware failure after SSRF. METHODS A multicenter, retrospective study was performed by a group of surgeons with a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 8 publications
1
19
1
Order By: Relevance
“…Furthermore, tissue inflammation and edema of both lung parenchyma and thoracic wall soft tissue peak at approximately 72 hours after injury with dissection often being bloodier and more challenging as compared to early SSRF (75). Also, hardware implantation in patients who have had recent pneumonia or empyema might lead to infected hardware, often requiring an additional operative procedure of implant removal (76,77). Practice patterns and consensus statements appear to be shifting towards early SSRF.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Furthermore, tissue inflammation and edema of both lung parenchyma and thoracic wall soft tissue peak at approximately 72 hours after injury with dissection often being bloodier and more challenging as compared to early SSRF (75). Also, hardware implantation in patients who have had recent pneumonia or empyema might lead to infected hardware, often requiring an additional operative procedure of implant removal (76,77). Practice patterns and consensus statements appear to be shifting towards early SSRF.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…This has been described before in SSRF for nonunion, although there is insufficient literature to evaluate the rate of hardware failure in nonunion SSRF. However, it is larger than the 2% that was previously described in 1224 patients who underwent SSRF for acute rib fractures [20]. A plausible mechanism could be that in these patients, rib nonunions develop not solely due to instability of the fracture, since the plate breaks most likely because of a persistent nonunion.…”
Section: Discussionmentioning
confidence: 73%
“…In a multinational study, hardware failure occurred in 3% of cases. 15 Another single-center study found that 3.5% of SSRF patients developed hardware infection, with increased body mass index, LOS, and hemorrhagic shock positively associated with infection. 16 Thiels et al 17 specifically examined hardware infections after SSRF, reporting a rate of 4.1%, but did not cite data regarding need for readmission among these patients.…”
Section: Discussionmentioning
confidence: 99%